Headship as policy narration: generating metaphors of leading in the English primary school. (3rd April 2019) - Maguire, Meg; Braun, Annette
ABSTRACT: This paper explores how doing headship may be considered as a form of policy narration. A key role of the headteacher as policy narrator is to tell/sell a story about their school to themselves, their staff and the outside world of parents, inspectors and other stakeholders. The accounts they construct will depend to some extent on their perspectives, commitments and personal-professional identities as well as an interplay between national priorities and situated contexts. They will also depend on who they are speaking to and what they take to be a 'professional' response in relation to their policy work in school. Drawing on in-depth interviews with two experienced English primary school headteachers, Hazel and George, and Lakoff and Johnson's claim [1980. Metaphors We Live By . Chicago, IL: University of Chicago Press] that metaphors are not just linguistic devices, but technologies of reasoning and understanding, this paper explores the ways in which headteachers deploy different tropes to explain what it is that they do. Metaphors of leadership explored include headship as branding, persuasion and not dropping the ball as well as fighting and parenting although there is an absence of any direct political critique in these two accounts.